Case study of a patient with cervical cancer on postoperative day 1 after total hysterectomy and pelvic and para-aortic lymphadenectomy - Ziemiańska, Joanna; Matusik, Sara (Journal of Education, Health and Sport, 2026)
Cervical cancer remains one of the most common malignant neoplasms of the female reproductive system and constitutes a significant global health problem among women. The key etiological factor is persistent infection with oncogenic types of the Human papillomavirus (HPV), particularly types 16 and 18. Effective primary prevention (HPV vaccination) and secondary prevention (screening tests, including cytology and HPV testing) enable early detection of precancerous lesions and significantly reduce morbidity and mortality. Despite well-developed preventive programs, diagnoses at advanced stages are still observed. The treatment of cervical cancer is complex and burdensome, involving surgical methods (e.g., hysterectomy), radiotherapy, and chemotherapy. Therapy affects not only the patient’s physical condition but also her psychological and social functioning. In this context, nursing care constitutes an integral element of oncological management. It includes educational activities, preparation for treatment, perioperative care, monitoring for potential complications, symptom management, and emotional support. A holistic approach to the patient is essential for maintaining the highest possible quality of life and for effective adaptation to the disease and its consequences.